A Demographic Study of Fractures in Patients Presenting to A Tertiary Care Hospital in Peshawar Pakistan: A 10-Year Retrospective Analysis (Journal of Pakistan Orthopaedic Association, 2019)
ABSTRACTObjective: To determine the frequency, aetiology and age distribution of different fractures in patients presenting to a tertiary care center in Peshawar.Methods: This was a descriptive cross-sectional study, conducted at Rehman Medical Institute, Peshawar, Khyber Pakhtunkhwa in the months of March 2018 to September 2018. A total of 1829 records related to fractures were obtained from the hospital archives. All fractures from all causes were taken into consideration, with in-patient records from 2004 to 2014 period. Data obtained was entered into MS Excel 2013 and were analyzed through formulating pivot tables. Percentages of the site-based fractures with three sets of age brackets were determined.Results: The total fractures were 1829 in 72.9% (n=1334) males and 27.1% (n=495) female patients. Individuals in the age group 15 to 64 years were in majority (67.3%, n=1230). The most common site of fracture was femur (38%,n=695) and least common scapula( 0.3 % ,n=5). The most frequent (37.5%) cause of fracture was road traffic accident (RTA) and majority cases (29) were reported in 2013.Conclusion: A general trend of lower limb fractures followed by upper limb and spine can be depicted from the data at hand. The most commonly occurring fracture was that of the femur with majority of the patients involved being in the 15 to 64 years age group. These fractures occurred mainly due to road traffic accidents.